Multiple retrograde tracing methods compatible with 3DISCO clearing - Shuai Han; Dongdong Li; Yuhui Kou; Zhongguo Fu; Xiaofeng Yin (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
Exploring the spatial relationship of various neuron pools in the spinal cord is crucial and difficult due to its complexity. The single-labelling tracing and sectioning were employed in previous studies exploring the distribution of spinal motor neuron pools, which could only delineate one single motor neuron pool in one specimen and could not achieve intact-tissue observation. Here, with combination of neuroanatomy tracing techniques and the optical clearing technique, we developed a multiple retrograde tracing method compatible with 3DISCO clearing. Fluoro-Gold, Fluoro-Ruby, Cholera Toxin Subunit B, Alexa Fluor 488 and 647 Conjugate were injected intramuscularly in hindlimbs of C57BL/6 adults. After labelling, the harvested spinal cords were optically cleared by 3DISCO method and imaged using confocal microscope. There were positive signals of all four tracers and four motor neurons pools targeting injected muscles were labelled. Three-dimension model of four motor neuron pools was successfully reconstructed based on tomography images showing the spatial relationship of different neuron pools. In conclusion, using this method, we first delineated the spatial relationship of four different motor neuron pools targeting four skeletal muscles in one spinal cord at the same time, which provide a holistic view of motor neuron pools in the spinal cord.